(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2020)
The main aspects of the organic production export crediting are investigated in this article. As export crediting today is an extremely relevant and important issue in Ukraine, there is a wide base of research in this area. However, despite the number of developments, today there is no established mechanism for the organic production export crediting. Nowadays, the export of organic production in Ukraine is actively evolving, so it needs additional financial support for growth. One of the tools to support the export of organic products is lending. Therefore, the purpose of the study is to analyze the theoretical foundations and practical aspects of lending for organic exports. The current state of the export of organic products in Ukraine has been studied. The regional distribution of organic production export is determined. The main ways of export crediting are also investigated. The existing experience of crediting the export of organic production in Ukraine and the world is analyzed. In particular, one of the main tools for organic product export crediting has been identified. The problems faced by the producer of Ukrainian organic products are identified and ways to solve them are suggested. Prospects for the development of organic product export crediting in Ukraine are considered. Thus, the study presents recommendations that can be immediately used for practical implementation as a tool for organic product export crediting.